Scurry: Scurry # 1-3 - Smith, Mac (Comic book artist) (Portland, OR : Skybound Comet, 2023)
A group of house mice struggle to survive a long and strange winter. The humans are gone, the sun is rarely seen, and a cold, dark rain befouls everything it touches. The mice, long dependent on humans for food, stubbornly cling to their old ways, looting the nearby abandoned houses for any scraps they can find. Once, there was plenty to eat, but now the scavengers return empty-handed, or not at all. Food is scarce, but danger is everywhere. As supplies run low and many mice fall ill, desperation creeps in. With the colony at a breaking point, rumors of a wrecked truck filled with food give them hope, but it lies far beyond the forest, where even the cats won't go.
Chiefly illustrations.
Keywords: Mice -- Juvenile fiction; Survival -- Comic books, strips, etc; Adventure and adventurers -- Comic books, strips, etc; Mice -- Comic books, strips, etc; Mice -- Juvenile fiction; Survival -- Juvenile fiction; Action and adventure comics; Graphic novels